Ferris Bueller's day off [videorecording (DVD)] - Hughes, John, 1950-2009; Broderick, Matthew, 1962-; Ruck, Alan, 1956-; Sara, Mia; Jones, Jeffrey; Grey, Jennifer, 1960-; Sheen, Charlie; Stein, Benjamin, 1944- (Paramount Home Entertainment, 2006)
A high school student is determined to get a day off with his friends by outwitting his principal.